PENGARUH KOMUNIKASI INTERNAL TERHADAP KEPUASAN KERJA KARYAWAN BAGIAN PRODUKSI PADA PT. DUTA PALMA NUSANTARA SEI. KUKO, BENAI - Mena Sukriani; Kasmiruddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Internal communication is considered necessary to improve employee job satisfaction, because if the communication that exists between management and employees as well as fellow employees in harmony, it will create a pleasant climate so that employees can be comfortable in the work. The purpose of this study was to determine the effect of internal communications on employee job satisfaction in the production of PT. Duta Palma Nusantara Sei. Kuko, Benai, Kuantan Singingi.The method used in this research is a quantitative method. The sampling technique used was accidental sampling with a population of 135 people and the number of samples is 58 respondents. The data obtained through observation, questionnaires and interviews were measured using a Likert scale.The results of this research indicate that the influence of internal communications on employee job satisfaction in the production of PT. Duta Palma Nusantara Sei. Kuko shows the corresponding criteria.Keywords : The Influence, internal communication, job satisfaction.